Dealing with diversity : Sri Lankan discourses on peace and conflict - Frerks, Georg; Frerks, Georg, 1954-; Klem, Bart.; Nederlands Instituut voor Internationale Betrekkingen "Clingendael". (Clingendael : Netherlands Institute of International Relations, 2005)
Contributed articles.
Keywords: Ethnic conflict -- Sri Lanka; Culture conflict -- Sri Lanka; Tamil (Indic people) -- Ethnic identity -- Sri Lanka; Muslims -- Sri Lanka; Peace-building -- Sri Lanka